Modification of the Wingate anaerobic power test for rowing: Optimization of the resistance setting - Mandic, S.; Quinney, H. A.; Bell, G. J. (International Journal of Sports Medicine, 2004)
The purpose of the study was to determine the resistance factor that would elicit the highest peak 5 s and mean 30 s power output (PO) during a maximal 30 s anaerobic power test on a rowing ergometer. Thirty-one rowers (17 male and 14 female) were recruited based on the light-weight (LW) (6 male; age 23 ? 6 yrs and 6 female; age 19 +/- 2 yrs) and heavy-weight (HW) (11 male; age 24 ? 4 yrs and 8 female; age 27 +/- 8 yrs) rowing categories. Each group completed 5 randomized series of maximal 30 s sprints equivalent to the following forces: 58.9, 63.8, 68.7, 73.7 and 78.6 N for LW males; 83.5, 88.4, 93.4, 98.2 and 103.1 N for HW males; 29.4, 34.3, 39.2, 44.1 and 49.1 N for LW females; and 44.1, 49.1, 54.0, 58.6 and 63.8 N for HW females. The tests were performed on a Gjessing rowing ergometer modified to accommodate greater resistance settings and computer linked to obtain the necessary data. The peak 5 s and mean 30 s PO (W) were determined for each test. A relative load factor (RLF) for determining the amount of resistance to be applied was calculated based on body mass (BM). The RLF settings that elicited the highest peak 5 s PO were 0.109 and 0.102 kg x kg-1 BM for LW and HW male rowers and 0.111 kg x kg-1 BM and 0.076 kg x kg-1 BM for LW and HW female rowers, respectively. The RLF settings for eliciting the highest mean 30 s PO were 0.102 and 0.095 kg x kg-1 BM for LW and HW male rowers and 0.103 kg x kg-1 BM and 0.068 kg x kg-1 BM for LW and HW female rowers, respectively. A 30 second anaerobic test was also performed on a Concept II rowing machine for comparison and it was found to elicit a significantly lower peak 5 s but not 30 s PO in both male and female rowers. Our findings provide RLFs for assessing anaerobic power using a 30 s test in male and female rowers. As well, peak 5 s but not mean 30 s PO is underestimated using the Concept II rowing machine.